Move a graph, write the equation

A. Move a graph up 2 units

Move the original graph y=x up 2 units. The resultant graph is y=x+2.

   

Move the original graph y=Abs(x) up 2 units. The resultant graph is y=Abs(x)+2.

 

Move the original graph y=x2 up 2 units. The resultant graph is y= x2+2

       

Move the original graph y=sin(x) up 2 units. The resultant graph is  y=2+sin(x).

 

 

Move the original graph y=x3 up 2 units. The resultant graph is y= x3+2.

          

Move the original graph of the circle x2 + y2 = 4 up 2 units. The resultant graph is the circle x2 + (y-2)2 = 4.

 

 

                

 

Move the original graph of the ellipse 

x2/9 + y2/4 = 1 up 2 units. The resultant graph is the ellipse 

x2/9 + (y-2)2/4 = 1

   

Move the original graph of the hyperbola x2/9 - y2/4 = 1 up 2 units. The resultant graph is the hyperbola  

         x2/9 - (y-2)2/4 = 1  

 

Move the original graph of the exponential function y=2x up 2 units. The resultant graph is the exponential function  y= 2x + 2.

      

 

 

 

 

 

 

 

 

 

Move the graph to right 2 units:

Move the original graph y =x to the right 2 units. The resultant graph is y =x- 2.

             

Move the original graph y = lxl to the right 2 units. The resultant graph is y = lx- 2l.

       

 

Move the original graph y =x2 to the right 2 units. The resultant graph is 

y = (x - 2)2.

        

Move the original graph y =sin(x) to the right 2 units. The resultant graph is  y = sin(x-2).

 

        

 

Move the original graph y = x3 to the right 2 units. The resultant graph is y = (x 2)3.

         

Move the original graph of the circle x2 + y2 = 9 to the right 2 units. The resultant graph is the circle (x - 2)2 + y2 = 9.

           

 

Move the original graph of the ellipse

x2/9 + y2/4 = 1 to the right 2 units. The resultant graph is the ellipse 

(x-2)2/9 + y2/4 = 1

        

Move the original graph of the hyperbola x2/9 - y2/4 = 1 to the right 2 units. The resultant graph is the hyperbola 

(x - 2)2 /9 - y2/4 = 1

      

 

Move the original graph of the exponential function y=2x to the right 3 units. The resultant graph is the exponential function  

y = 2(x-3).

    

 

Back to Patterns in Mathematics
To order Don's materials
Mathman home